2020
DOI: 10.1016/j.apmr.2019.08.485
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Nonsurgical Treatment for Symptomatic Thumb Carpometacarpal Instability in Clinical Practice: A Cohort Study

Abstract: Objective: To describe outcomes of nonsurgical treatment for symptomatic thumb carpometacarpal joint (CMC-1) instability. Secondary, to evaluate the conversion rate to surgical treatment. Design: Prospective cohort study. Setting: A total of 20 outpatient clinics for hand surgery and hand therapy in the Netherlands. Participants: A consecutive sample of patients with symptomatic CMC-1 instability (NZ431). Intervention: Nonsurgical treatment including exercise therapy and an orthosis. Main Outcome Measures: Pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…In a comparative study, silversplints led to equal functional results compared with thermoplastic orthoses, but they were valued more highly on aspects of comfort and cosmetics (21)(22)(23)(24)(25). However, in the current study patients were not asked to value these aspects.…”
Section: Discussionmentioning
confidence: 69%
“…In a comparative study, silversplints led to equal functional results compared with thermoplastic orthoses, but they were valued more highly on aspects of comfort and cosmetics (21)(22)(23)(24)(25). However, in the current study patients were not asked to value these aspects.…”
Section: Discussionmentioning
confidence: 69%
“…Exercise therapy aims to prevent subluxation by optimizing joint positioning. 12 The use of orthotics can be coupled with exercise therapy to prevent joint subluxation and subsequent inflammation. Wouters et al 12 showed improved VAS pain scores after 3 months of conservative therapy but long term outcomes in nonsurgically managed patients have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment of thumb CMC joint instability can involve exercise therapy and orthotic usage. Exercise therapy aims to prevent subluxation by optimizing joint positioning 12 . The use of orthotics can be coupled with exercise therapy to prevent joint subluxation and subsequent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the hip joint, a dysplastic TMC joint can still be asymptomatic and does not always necessitate surgical intervention. However, if a TMC joint becomes symptomatic in the presence of a trapezial dysplasia, one could consider a corrective osteotomy to normalize trapezial inclination if the patient does not respond to conservative treatment (Wouters et al., 2020). As such, our results could be of interest in the preoperative planning of a trapezial osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Instability of the trapeziometacarpal (TMC) joint is a cause of thumb base pain in young adults (Eaton and Littler, 1973; Lane and Henley, 2001). The management of these patients remains challenging (Schoenaers et al., 2017; Wouters et al., 2020) due to their higher functional demands. The absence of an osteoarthritic joint also makes them unsuitable candidates for classic surgical procedures like total joint replacement or trapeziectomy.…”
Section: Introductionmentioning
confidence: 99%